2021
DOI: 10.3390/ijerph18073699
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences of Health Behaviors in the Risk of Metabolic Syndrome for Middle-Aged Adults: A National Cross-Sectional Study in South Korea

Abstract: This study examined gender differences in health behaviors for the risk of metabolic syndrome (MetS) among middle-aged adults using nationally representative data from the Seventh Korea National Health and Nutrition Examination Survey (2016–2018). The sample included data from 8677 middle-aged adults. The Health Practice Index measured health behaviors, including smoking, alcohol use, physical activity, sleeping, eating breakfast, working hours, nutritionally balanced diet, and mental stress. Complex sample mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The middle-age and senior periods are important stage in the prevention and management of MetS owing to the increased susceptibility of individuals to MetS during these periods [ 5 7 ]. In addition, the risk of CVD is notably increased in middle-aged and senior adults with MetS [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The middle-age and senior periods are important stage in the prevention and management of MetS owing to the increased susceptibility of individuals to MetS during these periods [ 5 7 ]. In addition, the risk of CVD is notably increased in middle-aged and senior adults with MetS [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that early stage prevention and intervention are very effective at preventing and reducing the severity of CVD [ 3 , 4 ]. The middle-age and senior periods are important stages in the prevention and management of MetS owing to the increased susceptibility of individuals to MetS during these periods [ 5 7 ]. The risk of cardiovascular disease is notably increased in middle-aged and senior adults with MetS [ 8 ], and as many as 50–60% of older adults have been reported to meet the criteria for MetS [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an institution must evolve a more holistic, total population health management (PHM) approach to identify high-risk individuals of MetS early and promote employee health [ 2 , 9 , 10 ]. There are multiple risk factors for MetS, such as demographic characteristics, e.g., being male [ 11 , 12 , 13 ] or a middle-aged or older adult [ 14 , 15 ]. In hospital health care settings, work schedules are commonly characterized by alternating shifts, which make hospital employees particularly vulnerable, as their jobs require them to work night or rotating shifts.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research indicated that individual characteristics, such as shift work, chronic disease, family history [ 17 ], higher body mass index (BMI) [ 13 , 18 ], and unhealthy behaviours [ 19 , 20 , 21 ], are associated with higher rates of MetS. In summary, past studies pointed out that being male, being a middle-aged or older adult, having chronic diseases, having greater family histories, participating in shift work, smoking cigarettes, drinking alcohol, and chewing betel nuts were correlated with MetS [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. In addition, some healthy behaviours, such as eating vegetables and fruits, drinking milk, and brushing teeth, were not mentioned in past studies of MetS.…”
Section: Introductionmentioning
confidence: 99%